Earthquake-resistant design of masonry buildings - Tomaževič, Miha (Series on innovation in structures and construction ;, 1999)
"An important part of this book is dedicated to the discussion of the problems of repair, retrofit and rehabilitation of existing masonry buildings, including historical structures in urban centres. The methods of strengthening masonry walls as well as improving the structural integrity of existing buildings are described in detail. Wherever possible, experimental evidence regarding the effectiveness of the proposed strengthening methods is given."--BOOK JACKET.